Transmission of trace metals from fuels to soot particles: An ICP-MS and soot nanostructural disorder study using diesel and diesel/Karanja biodiesel blend. (15th November 2020) - Morajkar, Pranay P.; Abdrabou, Moataz K.; Raj, Abhijeet; Elkadi, Mirella; Stephen, Sasi; Ibrahim Ali, Mohamed
Highlights: The transmission of toxic trace metals from fuels to soot generated from them is investigated. ICPMS for metals and HRTEM, XRD, and Raman analyses for soot nanostructures are used. Cu and Fe were dominant metals in diesel and soot, though with transmission of only 0.09%. The addition of 20% Karanja-biodiesel to diesel enhances transmission of toxic metals to soot. Biodiesel addition induces disorder in soot to enhance reactivity and metal trapping efficiency. Abstract: Despite benefits of biodiesel such as reduced soot emissions and enhanced combustion efficiency, it enhances NOx emissions and may emit toxic trace metals that are present in biomass. This investigation focuses on the transmission of trace metals from fuels (diesel, Karanja biodiesel, and diesel/biodiesel blend) to soots generated from them. The study finds that the addition of 20% Karanja-biodiesel to diesel enhances the transmission of toxic metals such as Zn, Sr, Cs, and Pb to soot by normalized factors, defined as the ratio of the transmission rate from diesel to its soot (%) and the transmission rate from blended fuel to its soot (%), of 17, 7, 58 and 3, respectively, as compared to diesel. Although Cu and Fe were dominant metals in diesel and its soot, their transmission from fuel to soot was only 0.09%, suggesting a preferential selectivity of some metals such as Zn, Sr, Cs, and Pb or the catalytic effects of some metals such as Fe and Cu on soot surface. The nanostructural investigation of soot using HRTEM, XRD, and Raman analyses confirm that the addition of Karanja biodiesel to diesel induces structural disorders in soot such as higher fringe tortuosity, shorter fringe length, and smaller primary particle diameter than diesel soot that enhance its reactivity and possibly the trapping efficiency of metals. A combination of greater degree of metal transmission from Karanja biodiesel-blended diesel fuel to soot and the increased nanostructural disorder and reactivity makes soot from such blend potentially more hazardous than diesel soot.